The Correlation between EFL Students’ Self-Confidence and English Speaking Anxiety of Pasifik Morotai University - M. Daud Batubara; Balqis Husain; Grifit Makatika (STAI Hubbulwathan Duri, 2022)
This study aims to identify the relationship between English speaking anxiety and self-confidence of students in the Morotai Pacific University English education study program. The research method used is a correlational quantitative and descriptive approach. A convenience nonrandom sampling technique was used to select the sample. The sample of this study consisted of 54 students of the English Education study program at the Pacific University of Morotai. This data was analyzed through the Pearson Correlation Test. The results showed that most of the students of the English Education Study Program at the Pacific University of Morotai were afraid or hesitant to make mistakes in front of classmates and even lecturers. It is proven by the average Fear of Negative Evaluation (FE) is 31.44. 2) Respondents in this study had a moderate level of anxiety. The correlation coefficient regarding speaking anxiety and students' self-confidence was found to be r= -0.018 at a significance level of p= 0.896. Based on these findings, it was stated that there was no significant relationship between English speaking anxiety and self-confidence in students of the English Education Study Program.